2016
DOI: 10.17352/jnnsd.000009
|View full text |Cite
|
Sign up to set email alerts
|

Current Pathogenetic Concepts of Vascular Cognitive Impairment

Abstract: The term vascular cognitive impairment designates a heterogenous group of disorders ranging from mild cognitive impairment to full-blown dementia -vascular dementia -resulting from cerebrovascular lesions involving various brain areas. Current clinical criteria show moderate sensitivity (50-56%) and variable specifi city (range 64-98%). The prevalence in autopsy series ranges from 0.03 to 58% (mean 8-15% in Western series, 22-35% in Japan). Major morphological types -multi-infarct and subcortical vascular ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…As lesões cerebrais vasculares compreendem as modalidades isquêmicas (infartos, microinfartos, lacunas, hiperintensidades da substância branca, espaços perivasculares alargados) e hemorrágicas (infartos hemorrágicos, hemorragias cerebrais e microhemorragias), que se apresentam de modo variável, não havendo uma lesão neuropatológica única para a caracterização do CCV, assim como não há critérios amplamente aceitos em relação à localização e quantidade necessária de lesões para o diagnóstico neuropatológico de CCV [34][35][36][37] . Diversos eventos neuropatológicos parecem contribuir para a ocorrência de DCV, entre eles, perda da integridade da substância branca com consequente desconexão entre áreas estratégicas para as redes cognitivas 16 , alterações da cascata de coagulação 38 , dos oligodendrócitos 39 , modificações das células endoteliais 40 , com alterações na perfusão sanguínea cerebral.…”
Section: Mecanismos E Fisiopatologiaunclassified
“…As lesões cerebrais vasculares compreendem as modalidades isquêmicas (infartos, microinfartos, lacunas, hiperintensidades da substância branca, espaços perivasculares alargados) e hemorrágicas (infartos hemorrágicos, hemorragias cerebrais e microhemorragias), que se apresentam de modo variável, não havendo uma lesão neuropatológica única para a caracterização do CCV, assim como não há critérios amplamente aceitos em relação à localização e quantidade necessária de lesões para o diagnóstico neuropatológico de CCV [34][35][36][37] . Diversos eventos neuropatológicos parecem contribuir para a ocorrência de DCV, entre eles, perda da integridade da substância branca com consequente desconexão entre áreas estratégicas para as redes cognitivas 16 , alterações da cascata de coagulação 38 , dos oligodendrócitos 39 , modificações das células endoteliais 40 , com alterações na perfusão sanguínea cerebral.…”
Section: Mecanismos E Fisiopatologiaunclassified
“…In addition, the variation in the prevalence of VaD between the eighth and tenth decades of life was not significant in one study (from 10.2 to 9.9%) [16,17]. Mixed dementia, on the other hand, showed that prevalence between these age groups increased, advancing from 4.7 to 7.1% of subjects [16,17]. Another study conducted in the USA showed that VaD was responsible for 21% of dementia cases among those 80 years of age, but this rate corresponded to only 16% of cases older than 80.…”
Section: Brain Vascular Changes and Cognitionmentioning
confidence: 88%
“…A European study, for example, showed that the prevalence of VaD reduced when populations aged 60 and 90 were compared-15 and 8.7%, respectively [16]. In addition, the variation in the prevalence of VaD between the eighth and tenth decades of life was not significant in one study (from 10.2 to 9.9%) [16,17]. Mixed dementia, on the other hand, showed that prevalence between these age groups increased, advancing from 4.7 to 7.1% of subjects [16,17].…”
Section: Brain Vascular Changes and Cognitionmentioning
confidence: 96%
“…Cerebral vascular injuries comprise the ischemic (infarcts, microinfarcts, lacunae, white matter hyperintensities, enlarged perivascular spaces) and hemorrhagic lesions (hemorrhagic infarcts, cerebral hemorrhages, and microhemorrhages), which present in a variable way, with no single neuropathological lesion characterizing VCI. In addition, there are no widely accepted criteria in relation to the location and number of lesions necessary for the neuropathological diagnosis of VCI [34][35][36][37] . Several neuropathologic events seem to contribute to the occurrence of VCI, including loss of white matter integrity with consequent disconnection between strategic areas for cognitive networks 16 , changes in the coagulation cascade 38 and oligodendrocytes 39 , and changes in endothelial cells with alterations in cerebral blood perfusion 40 .…”
Section: Mechanisms and Pathophysiologymentioning
confidence: 99%